Facilitating Research-Informed Educational Practice for Inclusion. Survey Findings From 147 Teachers and School Leaders in England - Brown, Chris; MacGregor, Stephen; Flood, Jane; Malin, Joel (Frontiers in Education, 2022)
This paper considers the engagement by teachers and school leaders in England in educational practices that are both ‘research-informed’ and supportive of inclusive education. We do so by seeking to understand the benefits, costs, and signifying factors these educators associate with research-use. In undertaking the study, we first worked to develop and refine a survey instrument (the ’Research-Use BCS survey’) that could be used to uniquely and simultaneously measure these concepts. Our survey development involved a comprehensive process that comprised: 1) a review of recent literature; 2) item pre-testing; and 3) cognitive interviews. We then administered this questionnaire to a representative sample of English educators. Although response rates were somewhat impacted by the recent Covid-19 pandemic, we achieved a sufficient number of responses (147 in total) to allow us to engage in descriptive analyses, as well as the production of classification trees. Our analysis resulted in several key findings, including that: 1) if respondents see the benefits of research, they are likely to use it (with the converse also true); 2) if educators have the needed support of their colleagues, they are more likely to use research; and 3) perceiving research-use as an activity that successful teachers and schools engage in is also associated with individual-level research use. We conclude the paper by pointing to potential interventions and strategies that might serve (at least, in the English context) to enhance research-use, so increasing the likelihood of the development and use of effective inclusive practices in schools.